The British - Ebbutt, M.I. (Maud Isabel) 1867- (New York Avenel Books : Distributed by Crown Publishers, 1986)
Sixteen stories from the eight century onward representing Britain's myths and legends, with explanatory material. Includes Beowulf, Cuchulain, and Robin Hood.
Previously published by George G. Harrap.
Keywords: Tales -- Great Britain; Folklore -- Great Britain; Legends -- Great Britain